2022
DOI: 10.14407/jrpr.2021.00290
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Model for Estimating Individual External Dose Based on Ambient Dose Equivalent and Life Patterns

Abstract: Background: After the Fukushima Daiichi Nuclear Power Station (FDNPS) accident, a model was developed to estimate the external exposure doses for residents who were expected to return to their homes after evacuation orders were lifted. However, the model’s accuracy and uncertainties in parameters used to estimate external doses have not been evaluated.Materials and Methods: The model estimates effective doses based on the integrated ambient dose equivalent (<i>H*</i>(10)) and life patterns, conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…(2022) obtained data for 148 days from 36 people by combining personal dose equivalent data and GPS location data to verify the accuracy of a simulation that considers lifestyle behavior patterns, as described in the next chapter. They discussed the differences between indoor and outdoor locations [ 21 ]. Other cases can be found where the number of subjects was small, but where actual doses were measured over a long period of time [ 22 ], or where internal exposure doses assessed by measuring radon concentrations indoors were compared with external exposure doses [ 23 ].…”
Section: Overview Of Methodology For Individual Dose Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) obtained data for 148 days from 36 people by combining personal dose equivalent data and GPS location data to verify the accuracy of a simulation that considers lifestyle behavior patterns, as described in the next chapter. They discussed the differences between indoor and outdoor locations [ 21 ]. Other cases can be found where the number of subjects was small, but where actual doses were measured over a long period of time [ 22 ], or where internal exposure doses assessed by measuring radon concentrations indoors were compared with external exposure doses [ 23 ].…”
Section: Overview Of Methodology For Individual Dose Evaluationmentioning
confidence: 99%
“…(2019) developed a method to calculate annual personal dose equivalents based on ambient dose rate information continuously measured by walking and driving surveys [ 9 ], location information and time spent in the area interviewed from residents, indoor and outdoor reduction factors, and conversion factors from ambient dose equivalent to effective dose. The accuracy of this method was evaluated by comparing it with information measured by personal dosimeters [ 21 ]. An example of the accuracy verification of this method obtained by the authors is shown in Fig.…”
Section: Overview Of Methodology For Individual Dose Evaluationmentioning
confidence: 99%
“…As shown in equation 1 , accounting for behavioral patterns, such as place and time of stay, conversion to the effective dose allows individual exposure doses to be estimated with a certain accuracy without long-term measurements using personal dosimeters [ 15 , 16 ]. Additionally, this calculation makes it possible to predictive assessment of individual exposure dose for residents who return to the ‘specific reconstruction reproduction base area (SRR Zone)’.…”
Section: Uncertainties For Simulationsmentioning
confidence: 99%
“…GPS information refers to the location and duration of stay and is recorded using tools such as GPS loggers and smartphones [ 16 ]. Since this method records actual behavior, it can only be used for retrospective evaluation and is difficult to apply to the predictive evaluation.…”
Section: Uncertainties For Simulationsmentioning
confidence: 99%
“…For this reason, we use the same expression in this study. The estimation of individual external dose includes methods [7][8][9][10][11][12][13][14][15][16][17][18][19][20] based on individual external dose data and methods [21][22][23][24][25][26][27] based on ambient dose rate data. Estimation of individual external dose using individual external dose data has been conducted by the national government, local governments, researchers, and others [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%